Correctness of Paxos with Replica-Set-Specific Views - Howell, Jon; Lorch, Jay; Douceur, John (JD) (2004)
We present a specification and proof of correctness for the Paxos replicated state machine consensus protocol in which replica-set-change is implemented with replica-set-specific views.